PENGARUH PROFITABILITAS, SOLVABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Nila Resa Ayu Septiana; Devi Permatasari (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to examine the effect of profitability, solvability, and liquidity on firm value, with firm size as a moderating variable. The population in this study consists of LQ45 companies listed on the Indonesia Stock Exchange for the period 2022–2024. The sample was selected using purposive sampling, resulting in 61 samples. This research uses secondary data obtained from the LQ45 company fact sheet listings on the indonesia stock exchange for 2022–2024, sourced from website indonesia stock exchange. Data were analyzed using moderation regression analysis with SPSS 25. The results show that profitability has a negative and insignificant effect on firm value, solvability has a positive and significant effect on firm value, and liquidity has a positive and insignificant effect on firm value. Firm size does not moderate the effect of profitability on firm value, but firm size moderates the effect of solvability on firm value. Meanwhile, firm size does not moderate the effect of liquidity on firm value.